2015
DOI: 10.1002/jbt.21718
|View full text |Cite
|
Sign up to set email alerts
|

Crocin Prevents Patulin‐Induced Acute Toxicity in Cardiac Tissues via the Regulation of Oxidative Damage and Apoptosis

Abstract: Patulin (PAT) is a mycotoxin produced by several species of the genera of Penicillium, Aspergillus, and Byssochlamys principally by Penicillium expansum. This mycotoxin is suspected to affect several organs including kidney and liver. However, its toxic effect on heart remains unknown. The present study investigated for the first time the cardiotoxic effect of PAT in mice. We demonstrated that PAT increased creatinin phosphokinase (CPK) level, induced lipoperoxydation and protein oxidation, and triggered the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that patulin induced oxidative stress 13 14 15 16 and p53 activation 17 18 19 . We first confirmed these findings in the cell line used in the present study.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have shown that patulin induced oxidative stress 13 14 15 16 and p53 activation 17 18 19 . We first confirmed these findings in the cell line used in the present study.…”
Section: Resultsmentioning
confidence: 92%
“…Oxidative stress was suggested to play a pivotal role in patulin-induced multiple toxic signaling 14 15 16 . Consistent with DNA damage, p53 was activated in response to patulin exposure both in vitro and in vivo 17 18 19 . However, the functional role of p53 in the regulation of ROS generation by patulin has not been addressed.…”
mentioning
confidence: 88%
“…This study indicated that crocins potentiated antioxidant capacity as it increased SOD and catalase (CAT) levels, and decreased MDA level, similar to vitamin E (Dianat et al ., ). In addition, it was indicated that crocin could inhibit patulin (PAT)‐induced acute toxicity in cardiac tissues through amelioration of oxidative damage in mice (Boussabbeh et al ., ). PAT increased CPK level, induced lipoperoxydation and protein oxidation, and triggered the activities of antioxidant enzymes such as SOD and CAT.…”
Section: Methodsmentioning
confidence: 97%
“…The effect of α‐crocin on PAT‐induced toxicity in human colon carcinoma (HCT116) and embryonic kidney cells (HEK293) was also examined. It was observed that antioxidant activity of crocins decreased endoplasmic reticulum stress activation and lipid peroxidation production (Boussabbeh et al ., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Patulin cardiotoxicity is sustained by a study on mice [25], which showed that patulin induced oxidative stress and cell apoptosis. These effects can also lead to alterations of cardiac functions.…”
Section: Resultsmentioning
confidence: 99%